2017
DOI: 10.2147/jvd.s123063
|View full text |Cite
|
Sign up to set email alerts
|

Determination of bilateral symmetry of carotid artery structure and function in children and adolescents

Abstract: We compared the symmetry of carotid arteries in youth with high-resolution ultrasound. Participants (n=230 (121 females),13.8 ± 2.9 years old) were assessed for: intima media thickness (cIMT), lumen diameter (cLD), incremental elastic modulus (cIEM), diameter compliance (cDC), cross-sectional compliance (cCSC), diameter distensibility (cDD), and cross-sectional distensibility (cCSD). No significant differences (P >0.05 all) were found for cIMT (0.49 ± 0.09 mm vs. 0.49 ± 0.08 mm), cIEM (1095 ± 382 mmHg vs. 1116… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In a previous study, bilateral symmetry of the vertebral level of CB was found in just 28% of cases [ 16 ]. Bilateral symmetry for different morphofunctional characteristics of the carotid arteries was determined in youth, and significant differences were found only for the carotid lumen diameter [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, bilateral symmetry of the vertebral level of CB was found in just 28% of cases [ 16 ]. Bilateral symmetry for different morphofunctional characteristics of the carotid arteries was determined in youth, and significant differences were found only for the carotid lumen diameter [ 17 ].…”
Section: Discussionmentioning
confidence: 99%